COMPARISON OF TWO CUTTING SAWS ON CUTTING FRONDS IN FIVE DATE PALM VARIETIES - AL-Sumaidaee, Saif Alden K. M.; Ali M. Abdul-munaim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Management of date palm is laborious andcostly, thus this work intended to study the two types of frond cutting saws (reciprocating saw andvibrating saw) investigated on three cutting parameters (noise intensity result from frond cutting, surface regularity or flatness of the cut region, andsome mechanical characteristics of the cutting process including longitudinal andradial compressive strength andstress measurement) applied on field grown five date palm varieties (Barhi, Bream, Khestawi, Tebarzal andZahdi).  Nested r&omized complete block design was implemented which included five date palm varieties as the main plot andthe type of saw as a sub-plot. Results indicated that both saws caused noise intensity y in accordance with st&ard permissible noise intensity. The highest was in Tebarzal variety while the lowest noise intensity occurred in Bream andthus this variety caused significantly lower noise intensity during cutting fronds than Tebarzal andBarhi. Vibrating saw achieved significantly better cut surface flatness than reciprocating saw. The least frond cut uniformity was reported in Tebarzal variety during using reciprocating saw, whilst the highest was recorded during cutting Bream fronds using vibrating saw. Concerning the radial compressive strength andstress, after the laboratory test it was noticed that the Tebarzal variety resulted in a significantly higher diagonal compressive andstress strength than others except Khistawi, Tebarzal variety recorded the highest radial compressive strength andlongitudinal compressive stress resulted in a significant difference with other varieties except Khistawi. Bream reported the lowest mechanical properties among other varieties, in contrast to Tebarzal which recorded the highest properties. From previous results, it is concluded that the above studied varieties retains mechanical properties differ from each other, which cause different performance of the pruning process.